Analisis Neraca Air Sub DAS Irigasi Wirway Kabupaten Sarmi Provinsi Papua - Ery Suhartanto; Lily Montarcih Limantara; Ariston Samosir (Balai Teknik Irigasi, 2012)
District Bonggo, Sarmi Regency is one of the technical potential of irrigated land in The Province of Papua are not utilized optimally. Given the ever increasing demand for rice and in line with population growth in annual Sarmi Regency ranged 8-10% (BPS Papua, 2010), Central River Region (BWS) Papua through a section of Planning and Program Development plans to make a program of irrigation areas in the District Bonggo, Sarmi Regency. The study was carried out at Inggi Subbasin, Wirway Watershed, Sarmi Regency of Papua Province. The results showed that an alternative irrigation water demand in selected alternative 4 at DI Bonggo based PTT that was created is to broad Ha 3200 irrigation water needs of a maximum of 7.45 m3/sc, for the vast 2500 ha of irrigation water needs of a maximum of 5.82 m3/sc, for the area of 2,000 ha of irrigation water needs of a maximum of 4.66 m3/sc, for the vast 1500 ha of irrigation water needs of a maximum of 3.49 m3/sc, and for the extensive 1000 ha of irrigation water needs of a maximum of 2.33 m3/sc . For domestic water needs of the average in Inggi Subbasin in the year 2026 amounting to 0.00394 m3/sc. Whereas the minimum discharge is available for a maximum of 2.46 and 0.12 m3/sc. The Efforts of irrigated water is not able to provide some alternative plans with broad regional Irrigation (DI). Alternative calculated based on planting time changes with 4 alternatives of planting begin, where alternative IV has lowest defisit.